Electron spin properties of carbon based manomaterials: metallofullerenes, nanotubes and peapods - Zaka, M (2011)
The successful utilization of carbon nanomaterials in future electron spin-based technologies is highly dependent upon the ability to control their assembly at the nanoscale to form tailored solid-state architectures. Spin active metallofullerenes (MFs), Sc@C82 and La@C82,/sub>, can be self assembled in 3D fullerene crystals or inside a carbon nanotube to form peapod structures. Single walled carbon nanotubes (SWCNTs) are an architect material to potentially allow the formation of 1-D spin chains. SWCNTs should be optimised to allow formation of spin chains and free of magnetic catalyst and carbon impurities, which have previously limited investigations of SWCNT spin properties. To address this, SWCNTs produced by laser ablation with a non-magnetic PtRhRe catalyst were purified through a multiple step centrifugation process in order to remove amorphous carbon and catalyst impurities. Centrifugation of SWCNT solutions resulted in sedimentation of carbon nanotube bundles containing clusters of catalyst particles, while isolated nanotubes with reduced catalyst particle content remained in the supernatant. Electron paramagnetic resonance (EPR) signals were detected only for samples which contained catalyst particles, with the ultracentrifuged SWCNTs showing no EPR signal at X-band (9.4 GHz) and fields ≤0.4 T. Integration of MFs into future devices requires a clear understanding of the nature of the spin and spin-spin interactions. Evaluating the spin properties of MFs, in both 3D (crystals) and 1D (peapods), will identify the spin-spin interactions and the affect of the surrounding SWCNT. Diluting spin active Sc@C82 and La@C82 MFs in a diamagnetic C60 matrix, between 0.4% and 100%, permitted the tuning of the mean fullerene separation and thus interfullerene spin interactions. In dilute concentrations of MFs the hyper ne structure was resolved in EPR and with increasing concentration exchange narrowing was observed as a single narrow EPR peak. Encapsulation of Sc@C82 MFs, of varying dilutions, into purified SWCNTs allowed formation of highly ordered 1-D array of metallofullerenes. Changing the spin environment from 3D crystal to 1D peapod resulted in the loss of the observed hyperfine structure in EPR. A single narrow peak was observed for Sc@C82:C60 peapods, indicating significant affect of the surrounding SWCNT structure upon the spin interactions of 1D metallofullerenes. Peapods of Ce@C82 showed a similar EPR signal, suggesting that the observed narrow peak arises from charge transfer between the MF cage and the surrounding SWCNT.